WDR11, a WD Protein that Interacts with Transcription Factor EMX1, Is Mutated in Idiopathic Hypogonadotropic Hypogonadism and Kallmann Syndrome - Kim, Hyung-Goo; Ahn, Jang-Won; Kurth, Ingo; Ullmann, Reinhard; Kim, Hyun-Taek; Kulharya, Anita; Ha, Kyung-Soo; Itokawa, Yasuhide; Meliciani, Irene; Wenzel, Wolfgang; Lee, Deresa; Rosenberger, Georg; et al. (American journal of human genetics, 2010)
By defining the chromosomal breakpoint of a balanced t(10;12) translocation from a subject with Kallmann syndrome and scanning genes in its vicinity in unrelated hypogonadal subjects, we have identified WDR11 as a gene involved in human puberty. We found six patients with a total of five different heterozygous WDR11 missense mutations, including three alterations (A435T, R448Q, and H690Q) in WD domains important for β propeller formation and protein-protein interaction. In addition, we discovered that WDR11 interacts with EMX1, a homeodomain transcription factor involved in the development of olfactory neurons, and that missense alterations reduce or abolish this interaction. Our findings suggest that impaired pubertal development in these patients results from a deficiency of productive WDR11 protein interaction.